Correlational study between model variables and observable quantities of magnetar-powered H-rich supernovae - Maffione, Nicolás Pablo (2019)
Fil: Maffione, Nicolás P. Universidad Nacional de Río Negro. Sede Antina. Laboratorio de Procesamiento de Señales Aplicadas y Computación de Alto Rendimiento; Argentina.